2007
DOI: 10.4321/s0210-48062007000900012
|View full text |Cite
|
Sign up to set email alerts
|

Valor de la biopsia gonadal en el diagnóstico de los desórdenes del desarrollo sexual

Abstract: VALOR DE LA BIOPSIA GONADAL EN EL DIAGNÓSTICO DE LOS DESÓRDENES DEL DESARROLLO SEXUAL La información proporcionada por la biopsia testicular en los estados intersexuales es primordial para la identificación, clasificación y detección precoz de neoplasias en estos pacientes. Antes de decidir una determinada opción terapéutica, los datos del estudio histológico de la biopsia gonadal deberán ser evaluados junto con los datos clínicos, genéticos, hormonales y moleculares. La diferenciación sexual es el resultado d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The protective system includes chain-breaking antioxidants capable of reducing oxidant radical levels and blunting the propagation of free radical chain reactions. Some studies have shown that infertile men have an impaired seminal plasma nonenzymatic antioxidant capacity than fertile ones, suggesting an association between decreased total antioxidant capacity and male infertility [12,13].…”
Section: Oxidative Stress and Reactive Oxygen Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective system includes chain-breaking antioxidants capable of reducing oxidant radical levels and blunting the propagation of free radical chain reactions. Some studies have shown that infertile men have an impaired seminal plasma nonenzymatic antioxidant capacity than fertile ones, suggesting an association between decreased total antioxidant capacity and male infertility [12,13].…”
Section: Oxidative Stress and Reactive Oxygen Speciesmentioning
confidence: 99%
“…The existence of an epididymal-specific form of glutathione peroxidase and a high concentration of SOD within the epididymis would support this. Potts et al [1999] [44] compared seminal plasma from normal and vasectomized men for total antioxidant activity, and thiol, ascorbate and uric acid content, individual antioxidants that are abundant in human semen [12]. Total antioxidant and thiol concentrations decreased in vasectomized men whereas ascorbic acid and uric acid concentrations were unchanged and are therefore not key exports of the epididymis.…”
Section: Lipid Peroxidation Of Spermatozoamentioning
confidence: 99%